Design of a human resource information system : case study of the department of local administration - Yupa Ekarintarakul; Kanchit Malaivongs; Marcus, M.J.; Prapaporn Tungsarote; Carl Duisberg Gesselschaft e. V. Germany (CDG) (Bangkok : Asian Institute of Technology, 1984)
This study presents the development of a human Resources Information System for the Department of Local Administration (LAD) of the Ministry of Interior of Thailand. The present personnel work of the LAD was analyzed and information requirements in term of personnel resource planning and administration are studied. The new system is designed following these requirements with an emphasis on providing timely and relevant information for personnel management. The system supports both batch and interactive processing; the former for the data entry and regular reporting while the latter for providing the administration with the facilities for urgent retrieval of certain information The normalization technique is used in designing the files for this system which results in altogether 15 files, each is used for a particular major requirement. The interactive part of the system was developed using COBOL language and VSAM file organization to demonstrate the usefulness of the proposed systems. The implementation of the system emphasizes on man-machine dialogue.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Engineering and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1984
Keywords: Manpower policy -- Data processing